Oral health-related quality of life in older adults in a health program in Envigado, Colombia, 2018 - Torres-Vanegas, Manuela; Cardona-Arango, Dorys (Revista Facultad de Odontología Universidad de Antioquia, 2020)
Introduction: the population of Envigado, Colombia, is currently aging, a situation that prompted the creation of the “Comprehensive Care Network” program [“Red de cuidado integral”]. In 2018, a baseline study was carried out to gather information on the older adults participating in the program, including sociodemographic variables and the general and oral health situation of participants, but the obtained information was not thoroughly analyzed. Therefore, the aim of the present study was to find the association of oral health-related quality of life (OHRQoL) and the demographic, social and health factors of the older adults participating in the program in Envigado in 2018, in order to provide information to facilitate intervention strategies. Methods: an observational descriptive cross-sectional study was conducted using secondary information sources, carrying out a census of the target population. Descriptive and bivariate analysis were made to determinate the associations, and a binary multiple logistic regression model was run, calculating prevalence ratio (PR) with 95% confidence intervals (CI). Results: the study showed that 54.2% of the program participants had a poor to bad OHRQoL. The conditions that most explain OHRQoL are multimorbidity and overall health status perception. Conclusions: The findings of this study suggest that promotion of health and prevention of chronic diseases strategies should be continued to avoid multimorbidity and improve the perception of general health in the elderly population.